Attainment and the Development of the Teaching Competence of Newly Hired University Teachers - Shaikhova, Bakhyt; Kumarbekuly, Sanat; Igissinova, Zhamal; Manapova, Saltanat; Tantybayeva, Batima (Journal of Ecohumanism, 2024)
The study aims to determine ways of acquiring and improvement of teaching competences of novice teachers. I used a quantitative method for initial research as it concentrates on the numbers and statistics that sustain an opinion of social actuality. This small survey has been carried out among 16 full-time novice teachers of Amanzholov University, Kazakhstan, who have graduated from the university and have worked as university teachers for five months. The literature review focuses on defining the competencies required for teachers and on methods of acquiring them. The study builds on the theory of Donnay and Romainville (1996), who argue in their research of teaching in higher education that teachers learn to teach at university through experience. According to the results of the data, it was revealed that most of the novice teachers develop teaching competencies while teaching and solving situational problems. The level of preparation of new teachers depends on practical hours spent in the classrooms with students and in preparation for lectures and assessment work. In addition, it was found that the development of teaching competencies is facilitated by the mutual work of more experienced colleagues and novice teachers. Also, the exchange of experience and discussions between novice teachers contributes to the development of analytical skills in teaching and self-reflection.